2019
DOI: 10.1186/s12964-019-0418-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released from neural progenitor cells and induced neural progenitor cells regulate neurogenesis through miR-21a

Abstract: Neural stem/progenitor cells (NPCs) are known to have potent therapeutic effects in neurological disorders through secreting exosomes. The limited numbers of NPCs in adult brain and the decline of NPC pool in many neurological disorders restrain the further use of exosomes in treating these diseases. The direct conversion of somatic cells into induced NPCs (iNPCs) provides abundant NPC-like cells to study the therapeutic effects of NPCs-originated exosomes (EXOs). Our recent study demonstrated that iNPCs-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 34 publications
0
67
0
Order By: Relevance
“…Interestingly, the method of obtaining stem cells influences the types of exosomes they secrete. Thus Ma et al [ 141 ] showed that induced exosomes (iEXOs) secreted from induced neural progenitor cells (iNPCs) stimulated the proliferation of neural progenitor cells (NPCs), as opposed to exosomes secreted by NPCs, which only possess a differentiating ability. This effect was mediated by miR-21, which is highly expressed in NPCs and in later stages of brain development [ 141 ].…”
Section: Type and Role Of Evsmentioning
confidence: 99%
“…Interestingly, the method of obtaining stem cells influences the types of exosomes they secrete. Thus Ma et al [ 141 ] showed that induced exosomes (iEXOs) secreted from induced neural progenitor cells (iNPCs) stimulated the proliferation of neural progenitor cells (NPCs), as opposed to exosomes secreted by NPCs, which only possess a differentiating ability. This effect was mediated by miR-21, which is highly expressed in NPCs and in later stages of brain development [ 141 ].…”
Section: Type and Role Of Evsmentioning
confidence: 99%
“…Thus, multiple synthetic or natural nanocarriers have been applied in miR-17~92 delivery, including aforementioned exosomes. Emerging evidence has implicated exosomes as an excellent natural platform for delivering miRNA into the CNS due to superior miRNAs preservation from the RNases, promising targeting capacity post equipping with homing molecules, ability to penetrate the BBB, low-or non-immunogenicity, and flexibility in administration routes [74][75][76][77][78]. These unparalleled characteristics make exosome-based miRNA delivery an interesting and important direction for the development of novel therapeutic strategies for treating neurological disorders.…”
Section: Mir-17~92 Family As Regenerative "Medicine"mentioning
confidence: 99%
“…In animals, extracellular RNAs are extensively described in mammalian biofluids. These molecules are known to be secreted followed by functional uptake into recipient cells [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In invertebrates, the presence of extracellular RNAs has been demonstrated in arthropods and nematodes, with a limited number of studies demonstrating functional RNA transfer [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Extracellular Rna-based Communicationmentioning
confidence: 99%